Influence of Statolon on Resistance of Mice to Influenza - Pindak, Frank F. (1969)
Various interferon inducers are known to elicit protection against lethal or infecting doses of certain viral agents. Because of the relatively high morbidity rate of influenza and its seasonal occurrence, we wished to determine whether statolon-induced interferon might be effective in controlling this disease. Mice were treated intraperitoneally with statolon and challenged with influenza A(2) virus by the intranasal route. Although interferon was present in the serum at the time of virus administration, no change in mortality rate was observed. There was, however, a significant increase in the mean survival time of treated animals. Similar results were obtained when Newcastle disease virus was used as the interferon inducer. To determine the effect of the route of challenge, other mice were treated with statolon or Newcastle disease virus and inoculated with mengovirus by the intranasal or intraperitoneal route. The results demonstrated that the treated mice were protected to similar degree against challenge by either route. It is suggested that the relative ineffectiveness of interferon in protecting mice against influenza is due to an intrinsic characteristic of the virus itself rather than the type of interferon induced or the route of virus challenge.